Gestión del Software ISP Adminer, de procesos administrativos de la empresa cable futuro en la ciudad de Duran. - Guerra Rodríguez, Leidy María (2023)
The present investigation refers to "Management of the Isp Adminer software, of administrative processes of the company Cable Futuro in the city of Durán" has the objective of analyzing the importance of modifying or implementing the management of administrative processes of the clients in the company Cable Futuro de the city of Duran. In addition to, the line of research to be used is "Communication and Information Systems, Entrepreneurship and Innovation" and Subline is "Intelligent Software and Hardware Technologies and Networks". On the other hand, the methodology to be used is of a qualitative approach, of a descriptive type and the techniques that were considered are the interview applied through the interview file instrument, the bibliographic research carried out through academic search engines and the observation made by part of the author of the investigation, which obtains as a result that, in the company, during daily activities, a large amount of knowledge is produced that could be useful in other related processes. However, often this knowledge is not documented or stored anywhere in the organization, remaining only in the memory of the people who experienced it. If it is not used periodically, there is a risk that it will be forgotten, it was possible to validate the processes of each stage, thus avoiding the final revisions of the development, it was also possible to show that by making the modifications and updates, everything would be organized, available and sure.